Deletion Mutants in COP9/Signalosome Subunits in Fission Yeast Schizosaccharomyces pombe Display Distinct Phenotypes - Mundt, Kirsten E. (The American Society for Cell Biology, 2002)
The COP9/signalosome complex is highly conserved in evolution and possesses significant structural similarity to the 19S regulatory lid complex of the proteasome. It also shares limited similarity to the translation initiation factor eIF3. The signalosome interacts with multiple cullins in mammalian cells. In the fission yeast Schizosaccharomyces pombe, the Csn1 subunit is required for the removal of covalently attached Nedd8 from Pcu1, one of three S. pombe cullins. It remains unclear whether this activity is required for all the functions ascribed to the signalosome. We previously identified Csn1 and Csn2 as signalosome subunits in S. pombe. csn1 and csn2 null mutants are DNA damage sensitive and exhibit slow DNA replication. Two further putative subunits, Csn4 and Csn5, were identified from the S. pombe genome database. Herein, we characterize null mutations of csn4 and csn5 and demonstrate that both genes are required for removal of Nedd8 from the S. pombe cullin Pcu1 and that their protein products associate with Csn1 and Csn2. However, neither csn4 nor csn5 null mutants share the csn1 and csn2 mutant phenotypes. Our data suggest that the subunits of the signalosome cannot be considered as a distinct functional unit and imply that different subunits of the signalosome mediate distinct functions.